Pelatihan Peningkatan Keterampilan Kader KB Tim Pendamping Keluarga (TPK) dalam Mengatasi Stunting di Kota Tegal - Damayanti, Fitriani Nur; Astuti, Rahayu; Istiana, Siti; Kusumawati, Erna; Janah, Aniatul (Jurnal Surya Masyarakat, 2023)
Stunting is included in the priorities of Indonesia's national development. Tegal City is a priority area for handling stunting. Collaboration is needed in assisting families at risk of stunting with various parties, one of which is the PKK cadres so that training is needed for PKK cadres to improve skills for data collection and identification of families at risk of stunting. The purpose of this training activity for family planning cadres is to increase the knowledge and skills of TPK in data collection and identification of the risk of stunting in the city of Tegal. Community service activities training in data collection and identification of families at risk of stunting were attended by family planning cadres in Tegal. After the data collection and identification training activities for family planning cadres the Family Assistance Team (TPK) showed (p = 0.000 <0.05) which means that there was a significant difference in the knowledge of family planning cadres before and after being given training on stunting risk identification and data collection. Stunting can be corrected if it occurs in the first two years of a child's age, but afterwards it will be difficult to correct, so cooperation is needed in stunting prevention. The Family Assistance Team (TPK), one of which is the Family Planning Cadre, is tasked with assisting families at risk of stunting in terms of stunting prevention.